6th AIAA Flow Control Conference 2012
DOI: 10.2514/6.2012-3054
|View full text |Cite
|
Sign up to set email alerts
|

Burst Frequency Effect of DBD Plasma Actuator on the Control of Separated Flow over an Airfoil

Abstract: The flow fields around NACA0015 airfoil, separation over which is controlled by a DBD plasma actuator are simulated by implicit large eddy simulation with compact difference scheme, and the burst frequency effect of DBD plasma actuator on the control of separated flow over the airfoil is discussed. The Reynolds number based on chord length is set to 63,000 and the angle of attack is set to 14 [deg]. The DBD plasma actuator is installed at the 0 % and 5 % chord length from the leading edge, and actuated in burs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In these studies [7,11,12,15,24,32,33], the optimum burst frequency was suggested to be 0.2-2.0, which was nondimensionalized by the freestream velocity and characteristic length scale (F f c ref ∕u ∞ ). On the other hand, Asada and Fujii [35] have shown that a nondimensional burst frequency F 6 is more effective than F 1. They suggested that the actuation with F 6 can promote the transition to turbulence at the laminar-separation shear layer more effectively; then, the turbulent mixing leads to an early reattachment of the flow.…”
mentioning
confidence: 96%
“…In these studies [7,11,12,15,24,32,33], the optimum burst frequency was suggested to be 0.2-2.0, which was nondimensionalized by the freestream velocity and characteristic length scale (F f c ref ∕u ∞ ). On the other hand, Asada and Fujii [35] have shown that a nondimensional burst frequency F 6 is more effective than F 1. They suggested that the actuation with F 6 can promote the transition to turbulence at the laminar-separation shear layer more effectively; then, the turbulent mixing leads to an early reattachment of the flow.…”
mentioning
confidence: 96%
“…Because of its simple structure and high responsivity, it have been received a lot of attention as the perspective control device, and many researches have proved the applicability of the plasma actuator for controlling separated flows around fluid machinery. [1][2][3][4][5] Since flowfields around stationary airfoils are main target of separation control in most of the previous studies, the discussions on the effectiveness of the plasma actuator on the dynamic flowfields around the moving airfoils had been limited. 6-10 Mitsuo et al 9 concludes that the lift enhancement during the pitching down is achieved by that the vortices generated by the plasma actuator bring entrainment of main flow.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially problematic in high-speed flows appearing in real applications. Two approaches have been proposed to overcome this problem: one is to use a burst signal for the driving voltage signal (hereafter referred to as the burst mode) (Asada and Fujii, 2012), the other is to use the PA as a device to generate vortices, i.e., a vortex generator-type plasma actuator (VG-PA), as shown in Fig. 2 (Jukes and Choi, 2013).…”
Section: Introductionmentioning
confidence: 99%